Proposals for curbing the boom-bust cycle in the supply of capital to emerging markets - John Williamson (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
This paper examines what might be done to limit the boom-bust cycle in the flow of capital to emerging markets. Although the paper accepts that some types of capital flow (notably foreign direct investment) are much less problematic in this respect than others (notably short-term bank loans), it argues that influencing the mix would have to be done by capital controls by capital-importing countries rather than supply-side policies. Where supply-side reforms might help is in making some types of flow less unstable: for example, the Buiter/Sibert proposal for a Universal Debt Rollover Option (which needs amendment to alter the term for which rollover might apply); allowing investors with fiduciary responsibilities to hold (though not to buy) bonds of sub-investment grade; penalizing put options in bond contracts and inserting collective action clauses; requiring foreign loans to be denominated in domestic currency; and modifying the remuneration practices of portfolio managers.
Keywords: F34; 330; capital flows; boom-bust cycle; UDROP; collective action clauses; Internationale Kreditvergabe; Schwellenländer